2009
DOI: 10.1111/j.1948-7134.2009.00008.x
|View full text |Cite
|
Sign up to set email alerts
|

Biting activity and host preference of the malaria vectors Anopheles maculatus and Anopheles sawadwongporni (Diptera: Culicidae) in Thailand

Abstract: Adult mosquitoes in the Anopheles maculatus group were surveyed from different regions of Thailand and five different species were morphologically identified, including Anopheles maculatus, Anopheles sawadwongporni, Anopheles notanandai, Anopheles dravidicus, and Anopheles willmori. Blood-feeding activity and host preference of two species, Anopheles maculatus and Anopheles sawadwongporni, were observed during a one-year period at Pu Teuy Village, Sai Yok District, Kanchanaburi Province, west-central Thailand.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 13 publications
4
28
0
1
Order By: Relevance
“…The reduction in birth weight (−140 g) was of the same magnitude as that reported for MiP elsewhere in the region [3], making lack of bed net use a possibly proxy for exposure to malaria in this study. However, it has been shown that mosquitoes in this region have a propensity to feed outdoors and at times when women are still active and not under a bed net [19, 20]. Therefore, the association between no bed net use and a higher risk of birth weight may be explained by confounding factors, which were not taken into account in the analysis, such as a lower socio-economic status, a lower education level and worse health practices in women who did not use a bed net.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in birth weight (−140 g) was of the same magnitude as that reported for MiP elsewhere in the region [3], making lack of bed net use a possibly proxy for exposure to malaria in this study. However, it has been shown that mosquitoes in this region have a propensity to feed outdoors and at times when women are still active and not under a bed net [19, 20]. Therefore, the association between no bed net use and a higher risk of birth weight may be explained by confounding factors, which were not taken into account in the analysis, such as a lower socio-economic status, a lower education level and worse health practices in women who did not use a bed net.…”
Section: Discussionmentioning
confidence: 99%
“…sawadwongporni are three species of the Maculatus Group that are known to occur in Vietnam. The Maculatus Group includes nine species in southern Asia that are difficult to distinguish morphologically due to overlapping anatomical characters [49], but despite this shortcoming they are considered to play a role in malaria transmission in several regions [51,61-63]. Anopheles maculatus and An.…”
Section: Discussionmentioning
confidence: 99%
“…Calves and pigs were chosen as young small animals and experiments were carried out with one calf, one pig, two goats, two dogs, and five chickens at a time under the bednet traps [34]. Every hour, all mosquitoes inside the bednet traps were collected by an electrical aspirator for 15 minutes per hour throughout the 12 hour period [64]. Collection time periods were subdivided into early evening (19:00~22:00), late evening (22:00~01:00), post-midnight (01:00~ 04:00), and pre-dawn (04:00~07:00) [64].…”
Section: Methodsmentioning
confidence: 99%
“…Every hour, all mosquitoes inside the bednet traps were collected by an electrical aspirator for 15 minutes per hour throughout the 12 hour period [64]. Collection time periods were subdivided into early evening (19:00~22:00), late evening (22:00~01:00), post-midnight (01:00~ 04:00), and pre-dawn (04:00~07:00) [64]. The staff was divided into four teams with three people in each team.…”
Section: Methodsmentioning
confidence: 99%